Modification of the physical and optical properties of the frustule of the diatom Coscinodiscus wailesii by nickel sulfate - Townley, H.E.; Woon, K.L.; Payne, F.P.; White-Cooper, H.; Parker, A.R. (Institute of Physics, 2007)
In this paper we demonstrate how the photonic properties of a diatom can be altered by growth with a metal pollutant. Both the optical and physical properties of the silica frustule of the diatom Coscinodiscus wailesii were affected by the presence of nickel sulfate in sea water. It was found that a sublethal concentration of the metal both significantly modified the size of the pores of the valves and quenched the intrinsic PL of the amorphous silica. Since cytoplasmic structures may be involved in determining the frustule architecture, we also present TEMs of nickel-grown diatoms and show the affected organelles. The ability to modify the properties of the frustule shows that mechanisms exist for the alteration of existing structures in nature to optimize specific characteristics for exploitation in biotechnological applications.